2012
DOI: 10.1007/s00402-012-1511-x
|View full text |Cite
|
Sign up to set email alerts
|

Is proximal femoral nailing a good procedure for teaching in orthogeriatrics?

Abstract: We conclude that proximal femoral nailing is an operation suitable for teaching purposes. However, patients between 71 and 80 years of age seem to be at an increased risk for cut-out if operated by a resident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
2
10
0
1
Order By: Relevance
“…These two factors are closely related to the surgeon's experience and skill; Biber et al [27] showed that the risk of screw cutout is increased with inexperienced surgeons.…”
Section: Discussionmentioning
confidence: 98%
“…These two factors are closely related to the surgeon's experience and skill; Biber et al [27] showed that the risk of screw cutout is increased with inexperienced surgeons.…”
Section: Discussionmentioning
confidence: 98%
“…Complications in the surgical treatment of elderly patients' hip fractures are frequent, with rates ranging from 8 to 40% according to the current literature [1,2,3,4,5]. In addition, the long-term results following hip fracture surgery are poor, including the loss of independence in approximately half of the cases [6] and mortality rates of up to 37% over the first year following surgery [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In response to such problem, bone cement-enhanced PFNA designs with perforated spiral blades may provide stronger fixation of fractured femoral head-neck ends, none of 59 patients was found to undergo screw cutouts, cut through, blade displacement, implant loosening or disruption during a mean follow-up of 4 months [33]. It should be pointed out that inadequate surgeon experience may also increase the risk of screw cutout [34].…”
Section: Discussionmentioning
confidence: 99%